Endovascular balloon occlusion of the aorta for placenta percreta during cesarean hysterectomy (Indian Journal of Case Reports, 2018)
The potential massive hemorrhage from placenta percreta requires large volumes of blood products to be transfused which are often not readily available for resuscitation and surgery, especially at rural centers. Multiple foreign case studies report the successful use of endovascular balloon occlusion of the aorta (EBOA) for the management of maternal hemorrhage. We present the first case of placenta percreta in India which was managed successfully by pre-operative placement of a balloon-tipped catheter in the aorta. Her hemodynamic status was well-controlled intraoperatively, and there were no post-operative complications. The surgical field was bloodless on balloon inflation allowing for surgical dissection and hemostasis; occult bleeders could be visualized and ligated by transiently deflating the balloon. Importantly, the transfusion requirements of this patient were drastically reduced. The authors propose that EBOA can be a staple modality in the pre-operative management of placenta percreta, especially in rural areas.